2020
DOI: 10.2147/itt.s245913
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dendritic Cell-Based Therapy Using LY6E Peptide with a Putative Role Against Colorectal Cancer</p>

Abstract: Introduction: Albeit early stage gastrointestinal (GI) carcinomas have a good prognosis if treated with surgery, diagnosis is often confirmed at a late stage and efficacious drugs are lacking. Recent progress in immune-based therapies has focused on dendritic cells (DCs), aiming to elicit tumor-specific responses by inducing immunological memory. Our previous microarray study indicated that a biomarker, termed lymphocyte antigen-6E (LY6E), is commonly overexpressed in two potentially lethal GI cancers: those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…These findings suggest that LY6E plays an important role in the regulation of immune infiltrating cells in CRC. The findings of similar previously performed studies have demonstrated that the LY6E peptide had the capability to provoke an immune response [35], specifically in modulating T cell activation and proliferation [30,36,37]. Another research shows that LY6E-loaded dendritic cells did efficiently stimulate T cell subtypes, and a significantly increased proportion of Th1 cells [35].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These findings suggest that LY6E plays an important role in the regulation of immune infiltrating cells in CRC. The findings of similar previously performed studies have demonstrated that the LY6E peptide had the capability to provoke an immune response [35], specifically in modulating T cell activation and proliferation [30,36,37]. Another research shows that LY6E-loaded dendritic cells did efficiently stimulate T cell subtypes, and a significantly increased proportion of Th1 cells [35].…”
Section: Discussionmentioning
confidence: 73%
“…The findings of similar previously performed studies have demonstrated that the LY6E peptide had the capability to provoke an immune response [35], specifically in modulating T cell activation and proliferation [30,36,37]. Another research shows that LY6E-loaded dendritic cells did efficiently stimulate T cell subtypes, and a significantly increased proportion of Th1 cells [35]. Thus, LY6E is an important molecule that can be used to target tumor antigens in multiple cancers.…”
Section: Discussionmentioning
confidence: 81%
“…The results suggested that DCs pulsed with LY6E peptide antigen strongly matured and activated T cells. 75 Tumor lysate and tumor-derived exosomes are also used to activate DCs, and the results show that they can induce T cell activation and proliferation. 76,77 Moreover, it avoids the limitation of antigen selection and is accepted widely by patients.…”
Section: Dc-based Cancer Vaccinesmentioning
confidence: 99%
“…Tokhanbigli et al pulsed DCs with LY6E peptide (a protein related to MHC class I/II) and then cocultured DCs with mouse splenocytes to assess the ability of DCs to activate T cells. The results suggested that DCs pulsed with LY6E peptide antigen strongly matured and activated T cells . Tumor lysate and tumor-derived exosomes are also used to activate DCs, and the results show that they can induce T cell activation and proliferation. , Moreover, it avoids the limitation of antigen selection and is accepted widely by patients. , All of these approaches have been successful and are simple and cheap.…”
Section: Dc-based Cancer Vaccinesmentioning
confidence: 99%
“…In addition, DCs are enhancers of the immune response and capable of T-cell activation. [ 7 8 10 11 12 14 15 16 17 18 19 20 21 22 23 24 ] In this review, the mechanism and efficiency of the human conventional type-1 DCs (cDC-1), OX40 + plasmacytoid DCs (pDCs), and DCs-derived exosomes were discussed. In addition, different combinations with DCs therapy such as combination with the monoclonal antibody (mAb), cytokine-induced killer (CIK) cells, adjuvants, chemotherapy (DC-based chemoimmunotherapy), and nanoparticles (NPs) were listed and explored for their effectiveness against cancer, especially against CRC.…”
Section: Introductionmentioning
confidence: 99%